IONIC LIQUIDS (ILs)-BASED ELECTROLYTES SYSTEM FOR LITHIUM ION BATTERIES - OLIVIA NANDIKA (NIM:20616035), ASTRID
Electrolytes system play an important part in Lithium Ion Batteries (LIBs) due its role in lithium ion (Li+) transport between anode and cathode. Commercial LIBs used organic carbonates compound electrolytes system, but these electrolytes are flammable and volatile. For these reasons, modification of electrolytes system with non-volatile, non-flammable compounds and has high conductivity becoming recent research focus. It is already known that ionic liquids have high conductivity and as non-volatile compound. Based on these properties, ionic liquids (ILs) expected to cover the lack of the organic carbonates-based electrolyte system in LIBs. The conductivity of electrolytes system which consists of dimethyl carbonate (DMC)/diethyl carbonate (DEC) (1:1, v/v) as organic solvent (OS) and imidazolebased ILs measured at various temperature. Meanwhile, the thermal stability of the electrolytes system also measured, and the redox properties of lithium ion in IL-based electrolyte system, was investigated. The electrolyte conductivity of [bmim][BF4]- based reached ~13 mS cm-1 at 20 °C which is 10000 times higher than DMC/DEC based only. Thermal analysis showed that decomposition temperature of the IL-based electrolytes reached 360 °C, which is more stable than organic-based only (~110 °C). Cyclic voltammetry measurement showed that the IL-based electrolytes with composition [bmim][BF4]: DEC: DMC (3:1:1) + LiBF4 0.2M has quasi-reversible redox reaction. Charge-discharge performance showed that LIBs cell with IL-based electrolyte has 2 times higher (67.38%) coulombic efficiency than organic based (25.76%). The existence of [bmim][BF4] affect the conductivity and thermal stability of elctrolytes system. Based on these results, a mixture between ILs and organic solvent has a potential to become a new electrolytes system in the next Lithium Ion Batteries. Keywords: Conductivity